Fusion of Fuzzy AHP in selecting material for drinking water bottle based on customer needs - Mohamed Noor, Ahamad Zaki; Md Fauadi, Muhammad Hafidz Fazli; Jafar , Fairul Azni; Zainudin, Siti Fairus (Asian Research Publishing Network (ARPN), 2017)
In this paper, selection of drinking water bottle material is to be selected. Therefore, to try out decision making tools efficiency, three methods have been used. The methods are fusion of Analytic Hierarchy Process (AHP) with Fuzzy logic with different membership function. The material selected are silicone, polypropylene, HDPE, LDPE and Tin. The criterion that being taken into consideration are price, density, tensile strength, thermal conductivity and electrical resistivity. Three methods have been carried out, and the weightage compared in the form of line graph. The best material gave by traditional AHP and trapezoidal AHP are Polypropylene, however triangular AHP gave LDPE is the best. But all three methods shows that tin is the least desirable when it does not satisfy all criterions.